Introduction to homeland security - Ramsay, James D.; Logan, Keith Gregory (Westview Press, 2012)
This book, prepared by academics and practitioners, explores the various subjects that comprose the homeland security discipline in a post-9/11 environment, including administration, intelligence, emergency management, terrorism and counterterrorism, environmental security, public health, and much more.